Motion controllers (Machine design, 1989)
Motion controllers can be divided into 4 basic types: chip-level, board-level, box-level, and dedicated controllers. Devices in each of these categories play a different part in motion control. Motion controllers built up from integrated circuits (IC) frequently use single-chip microcontrollers as the primary source of computing power. Manufacturers have also developed special-purpose ICs to handle tasks needed to implement both closed-loop motion control and motor speed control. Board-level motion controllers generally contain one or more circuit boards mounted in a card rack chassis. Several commercially available board-level computers are targeted specifically at servocontrol. In some facilities, computers called cell controllers provide coordination among individual workstations and computer-controlled machines. Programmable logic controllers are computer-based equivalents of relay panels that direct the operating sequences of processes or machines.